Gemcitabine promotes autophagy and lysosomal function through ERK- and TFEB-dependent mechanisms - Benoît Marchand; Marc-Antoine Poulin; Christine Lawson; Lee-Hwa Tai; Steve Jean; Marie-Josée Boucher (Cell Death Discovery, 2023)
Abstract Gemcitabine is a first-line treatment agent for pancreatic ductal adenocarcinoma (PDAC). Contributing to its cytotoxicity, this chemotherapeutic agent is primarily a DNA replication inhibitor that also induces DNA damage. However, its therapeutic effects are limited owing to chemoresistance. Evidence in the literature points to a role for autophagy in restricting the efficacy of gemcitabine. Autophagy is a catabolic process in which intracellular components are delivered to degradative organelles lysosomes. Interfering with this process sensitizes PDAC cells to gemcitabine. It is consequently inferred that autophagy and lysosomal function need to be tightly regulated to maintain homeostasis and provide resistance to environmental stress, such as those imposed by chemotherapeutic drugs. However, the mechanism(s) through which gemcitabine promotes autophagy remains elusive, and the impact of gemcitabine on lysosomal function remains largely unexplored. Therefore, we applied complementary approaches to define the mechanisms triggered by gemcitabine that support autophagy and lysosome function. We found that gemcitabine elicited ERK-dependent autophagy in PDAC cells, but did not stimulate ERK activity or autophagy in non-tumoral human pancreatic epithelial cells. Gemcitabine also promoted transcription factor EB (TFEB)-dependent lysosomal function in PDAC cells. Indeed, treating PDAC cells with gemcitabine caused expansion of the lysosomal network, as revealed by Lysosome associated membrane protein-1 (LAMP1) and LysoTracker staining. More specific approaches have shown that gemcitabine promotes the activity of cathepsin B (CTSB), a cysteine protease playing an active role in lysosomal degradation. We showed that lysosomal function induced by gemcitabine depends on TFEB, the master regulator of autophagy and lysosomal biogenesis. Interfering with TFEB function considerably limited the clonogenic growth of PDAC cells and hindered the capacity of TFEB-depleted PDAC cells to develop orthotopic tumors.